Periodical cicada emergence resource pulse tracks forest expansion in a tallgrass prairie landscape. Issue 7 (12th July 2019) - Whiles, Matt R.; Snyder, Bruce A.; Brock, Brent L.; Bonjour, Sophia; Callaham, Mac A.; Meyer, Clinton K.; Bell, Alex
Abstract: Understanding factors that influence resource pulses is an important aspect of ecosystem ecology. We quantified below‐ to aboveground energy and nutrient fluxes during the 2015 periodical cicada emergence from forest habitats in a tallgrass prairie matrix and compared results to our prior studies of the 1998 emergence in the same watershed. We estimated 35.2 million cicadas emerged across 159 ha in 2015, almost 2× more than the 19.6 million across 98 ha in 1998. The 2015 emergence resulted in below‐ to aboveground fluxes of 9.4 metric tons of ash‐free dry mass and 1.12 metric tons of N, both 2× greater than 1998. This corresponds to 59 kg C/ha and 7 kg N/ha in and adjacent to forested areas in 2015. Increased emergence in 2015 was a result of spatial expansion of cicadas, not higher densities. Periodical cicadas are expanding with forest habitats in this region. Cicadas expand into and oviposit in 40% of available forest habitat during each emergence. Accordingly, we predict the 2032 emergence will span 245 ha. Our study demonstrates how human alterations to a landscape, in this case forest expansion linked to fire suppression and reduced grazing, can alter the magnitude and extent of a resource pulse.